1989
DOI: 10.2307/3869039
|View full text |Cite
|
Sign up to set email alerts
|

Transcription, Organization, and Sequence of an Auxin-Regulated Gene Cluster in Soybean

Abstract: We have characterized a soybean gene cluster that encodes a group of auxin-regulated RNAs (small auxin up RNAs). DNA sequencing of a portion of the locus reveals five homologous genes, spaced at intervals of about 1.25 kilobases and transcribed in alternate directions. At least three of the genes are transcriptionally regulated by auxin. An increase in the rate of transcription is detected 10 min after application of auxin to soybean elongating hypocotyl sections. Each of the genes contains an open reading fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
100
0
2

Year Published

1989
1989
2003
2003

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(105 citation statements)
references
References 0 publications
3
100
0
2
Order By: Relevance
“…In all cases examined, SAUR genes encode short transcripts with highly conserved open reading frames that accumulate rapidly and specifically after auxin treatment. Soybean SAUR gene transcription can be detected as soon as 2.5 min after the application of auxin (28,32). We have demonstrated that corn Zm-SAUR1 is a rapid auxin-responsive gene as well.…”
mentioning
confidence: 75%
“…In all cases examined, SAUR genes encode short transcripts with highly conserved open reading frames that accumulate rapidly and specifically after auxin treatment. Soybean SAUR gene transcription can be detected as soon as 2.5 min after the application of auxin (28,32). We have demonstrated that corn Zm-SAUR1 is a rapid auxin-responsive gene as well.…”
mentioning
confidence: 75%
“…1. DST sequences were demonstrated to contribute to the instability of SAUR transcripts, which are among the most short-lived mRNAs in higher plants (16,18,33). In fact, two mutants (dst1 and dst2), characterized by a defect for DST-dependent degradation, display an elevated level of SAUR-AC1 mRNA (44).…”
Section: Zmsaur2 a Short-lived And Auxin-induced Nuclear Proteinmentioning
confidence: 99%
“…With one exception (AtSAUR11), all SAUR genes appear to lack introns (3). SAURs encode unstable mRNAs (14,15), and their high turnover rate may be due to a conserved downstream (DST) 1 element in the 3Ј-non-translated region of the mRNA (16,17) as well as elements within the coding region (9,18). There is evidence that SAURs are not only transcriptionally regulated but are also regulated at the post-transcriptional (19) and post-translational levels (13).…”
mentioning
confidence: 99%
“…On the basis of their expression properties, the SAUR genes have been implicated in auxin-induced cell elongation (6), and their transcripts appear to be constitutively unstable so that their abundance can be rapidly altered in response to transcriptional control by the plant hormone auxin (7). All unstable SAUR transcripts contain conserved DST sequences, so-called because of their location downstream of the coding region (5). A dimer of the DST element (8) or the 3Ј end of the Arabidopsis thaliana SAUR-AC1 gene, which contains a DST element (7), are sufficient to destabilize reporter transcripts in plant cells.…”
mentioning
confidence: 99%
“…The DST element is found in the 3Ј UTR of the small auxin up RNA (SAUR) transcripts, which are among the most unstable mRNAs in plants, having half-lives of 10-50 min (4)(5)(6). On the basis of their expression properties, the SAUR genes have been implicated in auxin-induced cell elongation (6), and their transcripts appear to be constitutively unstable so that their abundance can be rapidly altered in response to transcriptional control by the plant hormone auxin (7).…”
mentioning
confidence: 99%